Como você resolve # cosx + cos (3x) = 0 #?

Responda:

#x = pi/2, (3pi)/2, pi/4, (3pi)/4, (5pi)/4 and (7pi)/4#

Explicação:

Observe que #cos3x# pode ser reescrito como #cos(2x + x)#.

#cosx + cos(2x + x) = 0#

Agora usa #cos(A + B) = cosAcosB - sinAsinB#.

#cosx + cos2xcosx - sin2xsinx = 0#

Candidatura #cos2x = 2cos^2x -1# e #sin2x = 2sinxcosx#.

#cosx + (2cos^2x - 1)cosx - 2sinxcosx(sinx) = 0#

#cosx + 2cos^3x - cosx - 2sin^2xcosx = 0#

Use #sin^2x + cos^2x = 1#:

#cosx + 2cos^3x - cosx - 2(1 - cos^2x)cosx = 0#

#cosx + 2cos^3x - cosx - 2cosx + 2cos^3x = 0#

#4cos^3x - 2cosx = 0#

Fator:

#2cosx(2cos^2x - 1) = 0#

Nós temos

#cosx = 0#

#x = pi/2, (3pi)/2#

E

#cosx = +-1/sqrt(2)#

#x = pi/4, (3pi)/4, (5pi)/4 and (7pi)/4#

Espero que isso ajude!

Deixe um comentário